Is It so Severe for Social Entrepreneurship in a Transitional Economy? The Role of Work-Related Wellbeing and Political Connection in Shaping the Exit Intention - Jianing Dong; Jianing Dong; Xiao Wang; Xiao Wang; Xuanwei Cao; Xuanwei Cao; David Higgins (Frontiers Media S.A., 2022)
In the context of a transitional economy, there are much more studies with a heroic characterization of social entrepreneurs, whereas there is limited exploration of their less positive stories. A range of studies tried to address this issue, although very few delved into the "inner layer" (work-related mental health) to unveil the mechanism of how social entrepreneurs develop their intention to quit their businesses. With a sample of 196 social business owners from China, this research focuses on the prosocial motivation of social entrepreneurs as well as its impacts on their work-related wellbeing and thus their business exit intention. With the partial least squares structural equation modeling, this research finds that prosocial motivation decreased entrepreneurs' partial work-related wellbeing, increasing their exit intention, and the mediating effects among the three components of work-related wellbeing were different. Furthermore, this research finds that work-related wellbeing's impact on exit intention was largely stronger for the social entrepreneurs without political connections.